Adsorptive capacity of sawdust for the adsorption of MB dye and designing of two-stage batch adsorber - Markandeya; Singh A.; Shukla S.P.; Mohan D.; Singh N.B.; Bhargava D.S.; Shukla R.; Pandey G.; Yadav V.P.; Kisku G.C. (My University, 2025)
The use of low-cost locally available adsorbent, sawdust for the removal of methylene blue (MB) dye in a batch adsorber system has been investigated. The experimental data fitted best in Langmuir isotherm as compared to Freundlich and Temkin isotherms, showing maximum adsorption capacity of 76.92 mg/g. The study revealed that the adsorption of MB dye onto sawdust follows pseudo-second-order kinetic model and the same has been used in design of a two-stage batch adsorber by minimizing total contact time to attain a fixed percentage of MB dye removal. The minimum contact time required for the removal of MB dye with 99% efficiency has been found as 37.54 min. © 2015 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.